Air Traffic Management and Systems III Selected Papers of the 5th ENRI International Workshop on ATM/CNS (EIWAC2017) - Electronic Navigation Research Institute; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This proceedings provides novel concepts and techniques for air traffic management (ATM) and communications, navigation, and surveillance (CNS) systems. The volume consists of selected papers from the 5th ENRI International Workshop on ATM/CNS (EIWAC2017) held in Tokyo in November 2017, the theme of which was "Drafting Future Skies". Included are key topics to realize safer and more efficient skies in the future, linked to the integrated conference theme consisting of long-term visions based on presentations from various fields. The proceedings is dedicated not only to researchers, academicians, and university students, but also to engineers in the industry, air navigation service providers (ANSPs), and regulators of aviation.
Introduction to the Fifth ENRI International Workshop on ATM/CNS (EIWAC2017) -- Future airspace design by dynamic sectorization -- An approach for attribute- and performance-based evaluation of interdependent critical infrastructures -- Trajectory Mathematical Distance Applied to Airspace Major Flows Extraction -- Aircraft Safety Analysis using Generalized Polynomial Chaos -- Robust Optimal Trajectory Planning under Uncertain Winds and Convective Risk -- Optimal location of dynamic military areas within civil aviation traffic -- Coordinated Validation for SWIM Concept-Oriented Operation to Achieve　Interoperability -- Development of a Ground Subsystem Prototype for Ground-Based Augmentation System (GBAS) Approach Service Type D (GAST-D) and the Evaluation of Its Performance in a Low Magnetic Latitude Region -- Interoperability of the ENRI GAST-D Ground-Station Prototype with Different Airborne Software Implementations -- GBAS Interoperability and Multi-Constellation / Multi-Frequency Trials -- ADS-B latency estimation technique for surveillance performance assessment -- Jamming and Spoofing Protection for ADS-B Mode S Receiver through Array Signal Processing -- Automatic Detection of Airport Runway Area Based on Super-Pixel PolSAR Image Classification -- Wireless-optical signal converter utilizing stacked-patch antennas and electro-optic substrates -- Multiuser 5G Hot-Spots based on 60 GHz Leaky-Wave Antennas and WDM Radio-over-Fiber -- Millimeter-Wave Imaging for FOD Detection -- 300-GHz Bistatic Radar System by Radio Over Fiber Network Technology -- HF-START: Application in aid of radio communications/ navigation.
Keywords: Telecommunication; Aerospace engineering; Astronautics; Mathematical models; Mathematical optimization; Computational intelligence; Communications Engineering, Networks; Aerospace Technology and Astronautics; Mathematical Modeling and Industrial Mathematics; Optimization; Computational Intelligence